The Oral–Lung Microbiome Axis in Connective Tissue Disease-Related Interstitial Lung Disease - Bongers, Kale S.; Massett, Angeline; O'Dwyer, David N. (Seminars in Respiratory and Critical Care Medicine, 2024)
Connective tissue disease-related interstitial lung disease (CTD-ILD) is a frequent and serious complication of CTD, leading to high morbidity and mortality. Unfortunately, its pathogenesis remains poorly understood; however, one intriguing contributing factor may be the microbiome of the mouth and lungs. The oral microbiome, which is a major source of the lung microbiome through recurrent microaspiration, is altered in ILD patients. Moreover, in recent years, several lines of evidence suggest that changes in the oral and lung microbiota modulate the pulmonary immune response and thus may play a role in the pathogenesis of ILDs, including CTD-ILD. Here, we review the existing data demonstrating oral and lung microbiota dysbiosis and possible contributions to the development of CTD-ILD in rheumatoid arthritis, Sjögren's syndrome, systemic sclerosis, and systemic lupus erythematosus. We identify several areas of opportunity for future investigations into the role of the oral and lung microbiota in CTD-ILD.
Keywords: oral microbiome; lung microbiome; interstitial lung disease; connective tissue disease